Inter-fragmentary compression using cannulated cancellous screws augmented with modified tension band wiring in transverse patella fractures - Khemkar, Sachin M.; Pawar, Eknath D.; Gavhale , Sandeep V.; Kambli, Mrinal M.; Chavan, Vivek; Modi, Nihar (International Journal of Research in Orthopaedics, 2023)
The classical Kirschner wires and tension band wiring technique, described by the AO foundation, has been the most widely used method for transverse patella fractures. In this study, we have adopted what we perceive to be an improved technique, the cannulated cancellous screws with modified tension band wiring. 20 patients with transverse patella fractures were included in our prospective single-blinded randomized control study with a duration of 3 years. All patients were operated on with modified tension band wiring with a 4 mm cannulated cancellous screw. Functional evaluation was made using the Tegner lysholm knee scoring scale. Roentgenograms were taken in AP and Lateral views to look for signs of radiological union and interfragmentary gap. The post-operative interfragmentary gap between fracture fragments with 65% of patients having a 0 mm gap, 25% of patients having a 1 mm gap, 5% of patients having a 2 mm gap, and 5% of patients having a 3 mm gap. The mean duration for the radiological union was 10 weeks. Mean Tegner lysholm score at 6 months was 88±4.7. We concluded that modified tension band wiring with cannulated cancellous screw is a safe, reliable, and better alternative method of fixation for transverse patella fractures with excellent union rate, range of motion, and functional outcome.